Spatial-Temporal Changes and Influencing Factors of Regional Technological Innovation Efficiency in China: A Three Entity Comparative Perspective - Ye Lei; Zhang Ting; Cao Xianzhong; Zeng Gang (Redai dili)
To build world science and technology power, industry, universities, and research institutes must complement each other in technological innovation. Currently, China has not yet fully shifted from a university- and research-centered to an enterprise-centered innovation system. Investigating and comparing the spatiotemporal changes and influencing factors of technological innovation efficiencies of firms, universities, and research institutes to optimize the allocation of regional innovation resources and improve regional innovation policy is important. Using 31 provincial-level administrative regions in China as decision-making units, this study measures and compares the spatiotemporal changes in technological innovation efficiencies and the factors influencing the technical inefficiencies of the three entities using GIS spatial analysis and Stochastic Frontier Analysis. The main findings are as follows: 1) The technological innovation efficiencies of firms, universities, and research institutes show a steady increase over the study period, with a 45%-55% improvement space. Firms have the lowest technological innovation efficiency but the fastest growth rate in technological innovation efficiency. Firms are expected to surpass the technological innovation efficiency of research institutes in the next two years; however, there is still a large gap with universities, indicating that firms have not yet become key players in the innovation system. 2) The spatial differences between the technological innovation efficiencies of firms, universities, and research institutes are significant. Only a few provinces have formed a situation of industry-university research in tandem, suggesting a certain degree of spatial mismatch between technological innovation efficiency and regional economic development. Our analysis shows that regional differences in the technological innovation efficiency of innovation entities are closely related to regional innovation modes. 3) Technological inefficiency factors coexist in the regional innovation milieu and industry-university research cooperative innovation. The direction and magnitude of the impacts of exogenous environmental variables— infrastructure, market environment, labor quality, financial markets, and entrepreneurship—on technological inefficiencies vary with the type of innovation entity. Collaborative innovation among enterprises, universities, and research institutes has significant positive effects on technological innovation efficiency, except for research institutes technological innovation efficiency when collaborating with enterprises. The reason for the insignificant effect of enterprise-research institute collaborative innovation on research institutes' efficiency may be that both research institutes and firms consider technological application and development as the main goal of collaborative innovation, and collaborative innovation with firms crowds out the internal innovation resources of research institutes and inhibits their technological innovation activities. We contribute to the literature on regional innovation systems by comparing the differences in the technological innovation efficiency of the main innovation entities in the regional innovation systems of a transition economy. Our findings provide a basis for the rational allocation of technological innovation resources and the optimization of the regional innovation environment.